Mechanisms of visibility of rurality and border areas in Usme - Meneses-Baez, Alba Lucia; Casas-Matiz, Elvia Isabel (Frontiers in Built Environment, 2024)
The visibility of rurality contributes to optimize the planning and administrative management processes of the territories, by providing contextualized information on the relationship of the inhabitants with the area under study. The objective of this research is to identify the mechanisms of visibility of rurality in Usme, a locality of Bogotá, Colombia. A case study was carried out using a mixed methodology. Based on a literature review, conceptual categories that support the visibility of rurality were formulated and based on them, a perception survey, addressed to peasant leaders of Usme, was designed. The survey contained 22 questions that inquired about socio-demographic data, citizen participation, roles of the inhabitants, participation scenarios, conditions, institutions, opportunities for improvement and needs and processes of the locality; the questions were multiple-choice with a single answer and open-ended. The survey was sent to 50 peasant leaders, 36 of them filled it out (13 men, 21 women, 2 LGBTIQ) residents of low (25), medium (3) and high (8) localities of the rural zone of Usme. Using the program Atlas.ti, a frequency analysis was carried out for the multiple-choice questions and for the textual data, as well as a content analysis of deductive and emergent categories, the, a nomological network on mechanisms of visibility was constructed. The results show that participants understand rurality visibility mechanisms in terms of five dimensions: spaces of visibility, dimensions of rurality, forms of participation, places of participation and types of impact. The delimitation and definition of the dimensions that constitute the mechanisms of rurality visibility in the borders, contributes to the design of effective strategies to improve the conditions of the inhabitants of this area, as well as, their participation to increase the impact and coverage of the institutions of the territory, aiming to improve the quality of life of the inhabitants of the area. We concluded that, in order for this to happen, it is necessary to have community empowerment and social co-responsibility of the community, the civil institutions, and the government.